"It was better when it was worse": the Ostalgie and the DDR kitchen - Guttilla, Laura (E|C, 2020)
The article focuses on the renewed attention on the DDR gastronomy as a manifestation of the so called “Ostalgie” (a sort of nostalgia for the days in which East Germany used to be separated from West Germany). This nostalgic passion can be observed in three different discourses (the discourse of the city, that of the gourmet gastronomy and that of the touristic gastronomy) that interweave in the semiosphere of the culture and the memory of the East Germany history. The analysis aims at highlight the semiotic mechanism of this passion of “vintage” in the gastronomy sphere of the current German identity.